Electric Field-Based Cancer Therapy Induces the Expression of HMGB1 and PD-L1 mRNA Genes on Breast Tumor of Female Rats - Fathurrohmah, Siti; Cahyadi, G.A.B Yehezkiel P.; Alamsyah, Firman; Pratiwi, Rarastoeti (Indonesian Society for Cancer Chemoprevention, 2022)
Electro Capacitive Cancer Therapy (ECCT) is an electric field-based cancer therapy method using intermediate frequency (150 kHz) and low intensity (18 Vpp). High Mobility Group Box 1 (HMGB1) is a cytokine related to damage-associated molecular patterns (DAMPs) secreted by dead cells. The expression of Programmed Death Ligand 1 (PD-L1) is ligand present on the surface of tumor cells and its expression is associated with the increase in the number CD8+ T lymphocytes. This study aims to examine the effect of ECCT exposure on the expression of HMGB1 and PD-L1 genes on the breast tumor, brain, and liver tissues of Rattus norvegicus (Berkenhout, 1769). The tissues were obtained from the previous studies stored in RNAlater (-20˚C). Female rat tissues of the previous study from four treatment groups, namely the control group (NINT), non-DMBA-induction with therapy (NIT), DMBA-induction with non-therapy (INT), and DMBA-induction with therapy (IT). Gene expression was analyzed using the RT-qPCR. Statistical t-test with a p<0.05 significance level was performed using GraphPad Prism 9.4.0 software. The result shows HMGB1 and PD-L1 mRNA genes were both significantly expressed in breast tumor samples. The liver and brain samples of normal rats did not show any significant changes in the activity of these genes after exposure to the electric field. This study indicates that exposure to electric fields may trigger the expression of HMGB1 and PD-L on the rat’s breast tumor samples. This study also provides information related to the safety of ECCT in healthy organs of female rats, especially the brain and liver.Keywords: ECCT, breast tumor, HMGB1, PD-L1, IFN- γ.